Synthesis of control system - problem of millennium - A I Diveev; K A Pupkov; E A Sofronova (RUDN Journal of Engineering Research, 2011)
The problem of synthesis of control system is considered. It is shown that classical statement of the problem does not provide satisfactory quality of control. The corrected statement of the problem where solution guaranties high quality of control for any initial conditions is proposed.